The answer would be m1 = m2
FBD of m1 is the sum of the forces in the y direction =
0
0 = T - m1*g
transposing:
m1*g = T
FBD of m2 is the sum of the forces in the y direction = 0
0 = T - m2*g
transposing:
m2*g = T
set them equal to each other and solve for m1
m1*g = m2*g
= m1 = m2
Explanation:
The force on individual mass would be downwards or descending and equal to the tension shaped by the other mass, which would be upward or rising by the act of the seamless pulley, so the forces cancel on each mass.